Characterization of the Bacillus stearothermophilus BR219 phenol hydroxylase gene. - Kim, I C (1995)
The catabolic genes pheA and pheB, coding for the conversion of phenol to catechol and catechol to 2-hydroxymuconic semialdehyde, respectively, have been cloned from Bacillus stearothermophilus BR219 into Escherichia coli. Following its localization on the 11-kb B. stearothermophilus DNA insert by deletion and expression analysis, the phenol hydroxylase gene pheA was subcloned as a 2-kb HindIII fragment, whose transformant expressed the enzyme after phenol induction and even more strongly after o-, m-, and p-cresol induction. In vitro transcription-translation experiments indicated that the phenol hydroxylase and catechol 2,3-dioxygenase enzymes are constituted of single subunits with molecular weights of 44,000 and 33,000, respectively. Nucleotide sequencing of the pheA gene revealed a strong similarity to flavin hydroxylases from Rhodococcus and Streptomyces species. Hybridization experiments indicated that the fragment containing PheA and PheB is located on a 66-kb plasmid in the parental thermophile.